Data mining and intervention in Calculus I - Manly, Ian (Kansas State University, 2018)
Many students have difficulty performing well in Calculus 1. Since Calculus 1 is often the first math course that people take in college, these difficulties can set a precedent of failure for these students. Using tools from data mining and interviews with Precalculus and Calculus 1 students, this work seeks to identify the different types of students in Calculus 1, determine which students are at risk for failure, and to study how intervention can help them succeed both in mathematics and in their college careers.
Keywords: Data miningCalculus; Intervention